Collective conceptualization of parental support of dual career athletes: The EMPATIA framework. - Kinga Varga; Ciaran MacDonncha; Laurence Blondel; Enrico Bozzano; Fabrice Burlot; Rute Costa; Nadine Debois; Dominique Delon; Antonio Figueiredo; Joerg Foerster; Masar Gjaka; Carlos Gonçalves; et al. (PLoS ONE, 2021)
Background This study aimed to use a concept mapping methodology to develop a European framework of the needs of parents/guardians (P/G) for supporting athletes combining sport and education (dual career, DC). Methods By means of a concept mapping methodology, 337 French, Irish, Italian, Portuguese, and Slovenian parents sorted and rated 80 potential statements associated to parenting DC athletes. Results Five distinct clusters emerged: 1. P/G' roles, needs and awareness to support athletes, including 22 statements (mean:3.7; range: 3.2-4.2 pt); 2. Requirements for effective planning of DC pathway, including 19 statements (mean:3.7; range: 3.2-4.5 pt); 3. Educational opportunity, including 13 statements (mean:3.5; range: 3.1-4.0 pt); 4. Policy and provision for DC, including 19 statements (mean:3.7; range: 3.1-4.2 pt); and 5. Athletes' lifestyle & self-management, including 7 statements (mean:4.0; range: 3.5-4.5 pt). Estimates of effect size (Partial eta-squared) were calculated for ANOVAs to assess the degree of variability on the statement importance ranking as the dependent variable accounted for by the demographic data. The concept mapping showed good validity (stress value: 0.11) and high reliability (rSHT: 0.99, rSHM: 0.98; rRR:0.98). One-third of the statements indicated differences (p<0.05) in relation to the P/Gs' gender and the athletes' education level, competition level and sport typology. Conclusion In synthesizing the opinions, experience and needs of P/Gs of DC athletes the present framework provided sound theoretical underpinnings to inform the development of an online educational programme for empowering parenting DC athletes (https://edu.empatiasport.eu/eng/), as well as be a foundation for future Pan-European DC research on how these statements interact with each other, in different European contexts.